ANALISIS INSTRUMEN EVALUASI MATA KULIAH IKATAN KIMIA - Rr. Ariessanty Alicia Kusuma Wardhani; Mohan Taufiq Mashuri (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2015)
The goal of this research is analyze the evaluation instruments used in the final exam of the semester .This analysis is the validity and reliability. Validity consists of the level of distress and distinguishing power. This research has done on the a chemical bond course for college students of education study chemical Islamic university of Borneo (Uniska Arsyad Muhammad Al-Banjary) of fourth semester of the academic 2014 .A method of collecting data on this research used engineering documentation. This research used methods descriptive quantitative. Quantitative analysis of multiple choice used iteman program version 3.0. A qualitative analysis of multiple choice to be in accord with all the aspects of matter (content), construction and structure of the sentences.Based on the results of that analysis known about final exam a chemical bond consisting of 27.5% difficult , 55% easily enough , 15% easy and 2.5 % very easy. The overall difficulty exam level is good enough .The analysis result of differentiating resources there are about 10% bad , 25% good enough , 47.5% good and 17.5 % excellent. Based on the results, it’s just good enough , good and very good that can be used once . The reability analysis result is 0,854 indicates that final exam chemical bond given to students having high precisionBased on research can be concluded that validity test in accordance with the standards test but required improvement some questions. The questions is on a good enough level of difficulity